Analisis Kurikulum pada Mata Pelajaran Sejarah Kebudayaan Islam pada Madrasah Aliyah - Latifah, Leti (Epistemic: Jurnal Ilmiah Pendidikan, 2024)
Understanding the history of Islamic civilization is crucial in addressing modern challenges. This research aims to analyze the Prophet Muhammad's preaching strategy in Mecca and its presentation within the Islamic Cultural History (SKI) curriculum. Employing a descriptive qualitative research design, data were collected through document analysis and interviews with key informants at MAN 1 Cianjur during November and December 2023. The findings reveal that the SKI curriculum effectively integrates historical and religious values, enhancing students' understanding of Islamic history and moral development. The Independent Curriculum's flexibility allows for the incorporation of diverse teaching methods and technological tools, fostering comprehensive evaluations. This research supports previous findings on the importance of contextually relevant pedagogical approaches and contributes new insights into curriculum development for Islamic education. Future research should explore the long-term impacts of this curriculum model and its adaptability to different educational contexts, potentially guiding further enhancements in teaching Islamic history and values.